Ways to conduct lessons for children with speech disabilities with innovative technologies - Jumaniyova Lobar; Salamova Feruza (Genius Journals, 2022)
Speech problems in children are one of the most widely studied topics in science. Performing speech exercises from a child’s early age can prevent him or her from developing speech-related defects in the future. In this article, the author describes in detail the work on speech defects in children, the use of innovative technologies in their treatment
Keywords: Speech Problems; Treatment; Innovation Technologies; Manological Speech